2017
DOI: 10.3390/jimaging4010007
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Quantitative Crystallographic Information from the Wavelength-Resolved Neutron Transmission Analysis Performed in Imaging Mode

Abstract: Current status of Bragg-edge/dip neutron transmission analysis/imaging methods is presented. The method can visualize real-space distributions of bulk crystallographic information in a crystalline material over a large area (~10 cm) with high spatial resolution (~100 µm). Furthermore, by using suitable spectrum analysis methods for wavelength-dependent neutron transmission data, quantitative visualization of the crystallographic information can be achieved. For example, crystallographic texture imaging, crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…It was found that the difference of crystallite size between the simulated and theoretical Tr (E ) was 3.8%. This difference is almost acceptable because the difference of 3.8% is much smaller than the difference of 20 -30%, which was discussed in the crystallite size analysis [22]. The difference of texture in this case was 1.3%, and this is acceptable because of the same reason above.…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…It was found that the difference of crystallite size between the simulated and theoretical Tr (E ) was 3.8%. This difference is almost acceptable because the difference of 3.8% is much smaller than the difference of 20 -30%, which was discussed in the crystallite size analysis [22]. The difference of texture in this case was 1.3%, and this is acceptable because of the same reason above.…”
Section: Resultsmentioning
confidence: 58%
“…In particular, the crystallite size was strongly affected, and the difference of the analyzed values reached to about 20%. In an example of the crystallite size analysis [22], the crystallites of welded and unwelded α-iron plates were evaluated, and then discussed the 20 -30% difference of crystallite size. The difference of 20% in analyzed values, which was caused by the 4.7 K change of T moderator , possibly cause incorrect evaluation of the crystallite size.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These Bragg edge features in the transmission spectra probed by wavelength resolved neutron imaging enable mapping and local analyses of crystalline phases and strains in 2D [33] and 3D [34,35]. As such, neutron diffraction contrast imaging can complement conventional neutron diffraction, and due to its superior spatial resolution it is ideal for investigating complex sample geometries, phase distributions and corresponding lattice strain fields [32,[34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Bragg-dip imaging for single-crystal samples, such as Bragg-edge imaging for polycrystalline samples, can easily acquire two-dimensional crystal information. (7,8)…”
Section: Introductionmentioning
confidence: 99%